Design and Implementation of Smart Home Energy Management System Based on GSM Network - Saleh, Noor H.; Mubdir, Bilal A.; M. Al-Hindawi, Asaad M.; Ahmed, Adel H. (Kurdistan Journal of Applied Research, 2017)
The aim of this research is to design and implement a prototype of a home energy management system based on SMS service on GSM network. The proposed system can remotely monitor and control the home appliances using a mobile phone. The proposed system consists of a microcontroller connecting home appliances and lighting through sensors and relays. The microcontroller is also connected with a GSM module to support this system operate with an existing GSM network. This system is implemented using a GSM module that is connected with the personal computer representing the designed microcontroller. The home appliances, sensors and relays are modeled and simulated using Visual Basic programs. Software programs are developed and built into the personal computer to activate and control the home appliances according to received commands from the user mobile phone or to monitor and send their status to the mobile phone according to user request. The implemented system is tested practically with several cases at different times and it operates successfully with reasonable flexibility and secure operation. A good compatibility of the developed programs is achieved, since the system is running continuously without interruption under normal conditions of GSM network operation. It is found that the execution times for control and monitoring massages are 19.63 seconds and 19.33 seconds respectively.